Photosynthetic Bacteria in the Marine Environment at Porto Novo - DHEVENDARAN, K (Fishery Technology, 2017)
Sediment and water samples were coiiected from mangrove and estuarine biotopes at fortnightly intervals. The physico-chemical characters of the overlying water were studied. In the mangrove biotope maximum temperature (31.5Â°C) and in the estuarine biotope maximum salinity (35.6% 0 ) were recorded during the summer season, whereas in post-monsoon period the sulfate content was increased to 516 p.p.m. and the pH was reduced to 7.4. Invariably both in the enriched sediment and water samples four major peaks (at wavelengths 460, 705, 772 and 850 nm) and two minor peaks (at wavelengths 580 and 663 nm) of absorption spectra were noticed. A pure culture of Chromatium sp., isolated from mangroves sediment, showed three peaks of absorption spectra at wavelengths, 500, 580 and 850 nm. The effect of sodium chloride on the growth of Chromatium sp., was also studied and it was observed that maximum growth occurred in the range 1%-3% sodium chloride concentration. This isolate was also capable of utilizing various sulfur and carbon compounds. Glycerol and glucose did not show any specific effect whereas pyruvate, malate and acetate increased the growth.